2005
DOI: 10.1897/04-640r.1
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance investigation of in vivo free radical formation and oxidative stress induced by 2,4‐dichlorophenol in the freshwater fishCarassius auratus

Abstract: In the present study, electron paramagnetic resonance coupled with spin-trapping technique was used, with alpha-phenyl-N-tert-butylnitrone (PBN) as a spin-trapping agent, to investigate free radical generation in freshwater fish with acute 2,4-dichlorophenol (2,4-DCP) poisoning. The PBN-radical adducts were detected in fish liver samples following treatments of 2,4-DCP (0.025, 0.05, 0.5, 5, or 25 mg/kg) 24 h after intraperitoneal (i.p.) injection and 2,4-DCP (0.5 mg/kg) at 2, 4, 8, 24, or 72 h after i.p. injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The characteristics of radical adducts can be identified from their hyperfine splitting constants recorded on the EPR spectrum. As reported, the • OH can be significantly induced by 2,4-dichlorophenol, TBBPA, naphthalene and phenanthrene in fish liver (Luo et al 2005;Shi et al 2005a;Shi et al 2005b;Sun et al 2006;Yin et al 2007). However, it has not been reported whether TBBPA can induce SOD superoxide dismutase, CAT catalase, GST glutathione-S-transferase, GSH reduced glutathione, GSSG oxidized glutathione, GSH/GSSG ratio of reduced glutathione and oxidized glutathione Significant different from control are indicated as * P \ 0.05, ** P \ 0.01 ROS and oxidative stress in earthworm species.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The characteristics of radical adducts can be identified from their hyperfine splitting constants recorded on the EPR spectrum. As reported, the • OH can be significantly induced by 2,4-dichlorophenol, TBBPA, naphthalene and phenanthrene in fish liver (Luo et al 2005;Shi et al 2005a;Shi et al 2005b;Sun et al 2006;Yin et al 2007). However, it has not been reported whether TBBPA can induce SOD superoxide dismutase, CAT catalase, GST glutathione-S-transferase, GSH reduced glutathione, GSSG oxidized glutathione, GSH/GSSG ratio of reduced glutathione and oxidized glutathione Significant different from control are indicated as * P \ 0.05, ** P \ 0.01 ROS and oxidative stress in earthworm species.…”
Section: Discussionmentioning
confidence: 53%
“…Many studies argued that the GSH/ GSSG ratio was a good indicator for the level of oxidative stress (Halliwell and Gutteridge 1999;Lange et al 2002). Luo et al (2005) also reported a decrease in GSH/ GSSG ratio in fish liver exposed to 2-chlorophenol. In our study, the GSH/GSSG ratio was noted to have a significant decline at 0.1-1.0 mg L -1 TBBPA ( Table 1), suggesting that the oxidative damage occurs in the earthworms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A six line spectrum of three groups with two hyperfine coupling splitting peaks was observed. According to previous literature [4,5,13,16], the trapped ROS was likely to be the hydroxyl radical (·OH) and the levels could be expressed with the second couplet intensity of the triplets in the EPR spectra. Figure 2 showed the kinetics of ·OH generation over Considering the speed and the maximum of ·OH accumulation, POEA is supposed to be more toxic than the other two substances.…”
Section: Free Radical Production By Induction Of Roundup® Gis and mentioning
confidence: 91%
“…Researches suggest that reactive oxygen species (ROS), can be induced in organisms exposed to some environmental contaminants [4][5][6]. Recent study suggested that Roundup® might induce oxidative stress in aquatic organisms through the increased levels of tissue lipid hydroperoxides [7].…”
Section: Introductionmentioning
confidence: 99%